Pengaruh Kadar Sari Buah Stroberi (Fragaria vesca L.) Terhadap Kualitas Masker Gel Peel Off - juliana putri (Universitas Negeri Jakarta, 2021)
A mask is a depth-cleansing cosmetic which works deeply because it can remove dead skin cells. The characteristics of a face mask can be recognized by its texture that can be smeared on the surface of face skin, causing a feeling of tightness on skin, and containing useful substances for skin’s health. This study aims to examine the effect of strawberry juice levels on the quality of peel off gel masks. This study also applied experimental research method. The independent variable in this study is strawberry juice with concentrations of 10%, 15%, and 20%. Meanwhile, the dependent variable is the quality of strawberry juice peel off gel mask preparation level. The data collection technique used is an observation method through pH test, organoleptic test, as well as hedonic test which are conducted by three pharmacist lecturers. Meanwhile in analyzing the data, normality test, with the SPSS program, and Friedman test are applied. Findings suggest that strawberry juice can be formulated in a peel off gel mask with concentration variations of 10%, 15%, and 20%. The result of organoleptic test and hedonic test also show that the best concentration of peel off gel mask is the formula 3 with 20% strawberry juice. Meanwhile, the pH test result indicates that all the peel off gels produced meet the skin pH criteria, within the range of 4,5 to 7, and is compliant with the expected normal pH range.